Diarrhea Recurrence in Patients with Clostridium difficile-Associated Diarrhea: Role of Concurrent Antibiotics. (1999) - Alfa, MJ; Harding, GKM; Ronald, AR; Light, RB; MacFarlane, N; Olson, N; DeGagne, P; Kasdorf, K; Simor, A; MacDonald, KS; Louie, L
Abstract : OBJECTIVE: To monitor prospectively patients with Clostridium difficile -associated diarrhea (CAD) in a six hundred bed tertiary care hospital to determine which factors influenced the recurrence of the diarrhea. DESIGN: A prospective, nonrandomized study. After an initial diagnosis of CAD, patients were interviewed, and each week stool samples and environmental samples were monitored for the presence of toxigenic C difficile for as long as the patients remained in hospital. The relationship of concurrent antibiotics, prolonged fecal excretion of organism or toxin, and environmental contamination was assessed. PATIENTS: Over a two-and-a-half year period, 75 consecutive patients with CAD were selected and those who gave their written informed consent were enrolled. A control group to evaluate environmental contamination consisted of 75 patients with diarrhea not associated with C difficile . RESULTS: Of the 75 CAD patients, 11 (14.7%) had a recurrence of their diarrhea. Diarrhea recurrence was associated with an increased rate of prolonged excretion of toxigenic organism and/or C difficile toxin(s) (nine of 11 [81.8%] compared with nine of 64 [14.1%]; P≤0.0001; relative risk 14.25; 95% CI 3.383 to 60.023). The risk of diarrhea recurrence was not related to a specific antibiotic but to concurrent therapy. Treatment within 30 days of initial CAD-specific treatment with an antibiotic other than metronidazole or vancomycin occurred significantly more frequently in patients with recurrence of diarrhea compared with those who did not have a recurrence (eight of 11 [72.7%] compared with 22 of 64 [34.4%], P=0.022; relative risk 4; 95% CI 1.153 to 13.881). The environmental contamination rate for toxigenic C difficile in week one in the rooms of patients with diarrhea not caused by C difficile was low (two of 75 [2.6%]) compared with week one data for patients with CAD (14 of 75 [18.7%], P=0.002; relative risk 1.922; 95% CI 1.479 to 2.498). The most frequent site contaminated was the bedpan sprayer (eight of 14 [57.1%]). Pulsed field gel electrophoresis analysis of stool and environmental toxigenic isolates indicated that there was not a single endemic strain of C difficile . CONCLUSIONS: This study indicates that the recurrence of diarrhea may be related to concurrent 'other' antibiotics. Although data indicated that there was a correlation between diarrhea recurrence and prolonged fecal excretion of toxin, further studies are required to clarify the clinical significance.